Citizenship and Political Violence in Peru - Wilson, F. author. aut Link
XIII, 229 p.
Keywords: Exploring how restrictions on citizenship helped create conditions for political violence in Peru, this book recounts the hidden history of how local processes of citizen formation in an Andean town were persistently overruled, thereby perpetuating antagonism toward the state and political centralism in Peru.